TRI PUSAT PENDIDIKAN DAN LITERASI SEBAGAI ELEMEN STRATEGIS PENGUATAN KARAKTER DAN PENCERDASAN BANGSA - Luh Novi Kusuma Dewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The progress of the global world at this time brings a very significant impact on society,especially for Indonesian citizens.Positive impacts in various fields are greatly felt by thecommunity especially in the advancement of science and communication field. In line with thatcompetition in the global world has also become an important and important thing in followingthis rapidly changing, complex and unpredictable era. To follow the current global competition,building intelligent and qualified human resources is a big task for the Indonesian nation.However, creating good and competitive human resources is not enough to be done only throughcognitive reinforcement in the field of science and technology but it is also important to strengthenthe affective field. Therefore, the noble values of Pancasila related to morals and good moralsare also a matter that must be considered, should not be ruled out and should be inculcated inthe character of the nation so that negative impacts arising from this globalization can beminimized.Therefore, Tri Education and Literacy Center is the right and strategic element thatis needed to be used in an effort to strengthen the character and educate the nation of Indonesiain the development of the global era today.Keywords: Tri Education Center, Literacy, Character Education